Neoclassicism in Architecture and Poetry of the 1910s and 1910s: The Commonality of the Problem Field - Babadzhan, Svetlana G. (Actual Problems of Theory and History of Art, 2022)
The article attempts to compare the programs of Neoclassicism in Russian architecture and poetry of the 1900s and 1910s. The convergence of two unrelated types of art allows however to reveal the commonality of the problem field. The similarity was revealed in the following issues: the chronological boundaries of the style, ideological attitudes among neoclassicists, perception of historical tradition, actualization of the problem of mastery, and terminology used. The field of neoclassical poetics and architecture is also united by the contradictory goals of the style: the revival of the classical ideal is impossible in the situation of multidirectional stylistic trends of the art in the beginning of the century. The interdisciplinary analysis of the poetics and architecture of neoclassicism has allowed us to understand the position of architecture in the board context of neoclassical culture and to point out that the formation of the architectural style is determined by the unity of the artistic process.
Keywords: architecture of Russian Neoclassicism; neoclassicism; Russian architecture; 1910s; poetry of Neoclassicism